Domestic Space, Intimate Surprises: The Bonds and Bondage of Enslaved, Khoisan, and Settler Women in the 1825 Koue Bokkeveld Revolt - Mitchell, Laura J. (South African Historical Journal, 2024)
Household details that emerge from the criminal prosecution of participants in the 1825 Koue Bokkeveld Revolt afford an opportunity to trouble the way women's history has been written in South Africa. Rather than focusing on a race or ethnic group, a careful reconstruction of domestic space and concomitant relationships on a frontier farm allows us to see slave, Khoisan, and settler women through the same lens. Women forged bonds of affinity and enmity within and across hierarchies of age, race, labour status, and domestic service. Following women's relationships allows us to analyse enslaved and indentured labourers through the same lens. Although 12 of the 13 rebels were men and boys, the trial record reveals women's relationships and centres women's agency.